Estetika Sastra Populer dalam Film Remake Aladdin (2019) Produksi Disney - Rizki Eka Putri Alda (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2020)
This study aims to elaborate formulas in the movie Aladdin. The theories are the cultural production arena by Bourdieu and Disney's